Testing the hypothesis of Rothman and Salovey (1997) under a choice task, a time constraint and when decision making on the behalf of another - Tomlinson, Susan (2009)
The presentation of information is central to decisions to engage in a treatment and the uptake of health care behaviours. Hence understanding the processes which are responsible for framing effects within the health domain is crucial to achieving effective and unbiased communication. Within the message framing literature decision making is considered being a function of the valence of the information which is presented. Research has shown that individuals are more likely to attend a screening examination when information is presented as a loss a frame and more likely to engage in preventative behaviour when information is presented as a gain frame. However according to Rothman and Salovey (1997); Rothman, Kelly, Hertel, and Salovey (2003) it is the degree to which performing a health behaviour presents risk to the individual that determines whether a positively or negatively valenced version of information is more likely to be effective in encouraging the behaviour advocated. To date, studies assessing the hypothesis by Rothman and Salovey (1997); Rothman et al (2003) have only considered framing effects in the case of decision making for the self, and have not considered how framing of information may influence choice tasks. Additionally emotional reactions to risk information may play a part in determining the influence of framing effects (Lowe and Ferguson, 2003).